Examining the Cyber Victimization Situation of Secondary School Students According to School Types - Türker, Meltem; Bahçeci, Ferhat (Türk Psikolojik Danışma ve Rehberlik Derneği, 2025)
This study examines the cyber victimization levels of secondary school students based on school types, using the comparative research method, a quantitative design. Data were analyzed using SPSS software, and the study is considered significant for its potential contributions to preventive guidance by offering both remedial and educational insights. The sample includes 1,251 students from 13 schools: 6 Anatolian, 2 Imam Hatip, 1 Vocational, 1 Science, 1 Social Sciences, 1 Sports, and 1 Fine Arts high school. Sampling prioritized population representation, leading to a higher number of Anatolian high schools due to their prevalence. Data were collected using the 24-item Cyber Victimization Scale developed by Arıcak, Tanrıkulu, and Kınay (2012). Results showed that, in comparisons, Anatolian high schools performed better than Science high schools, while Imam Hatip high schools outperformed Anatolian high schools. The findings provide valuable insights for addressing cyber victimization in secondary education contexts.

Nicel araştırma desenlerinden karşılaştırmalı araştırma yönteminin uygulandığı araştırmada, ortaöğretim öğrencilerinin siber mağduriyet durumlarının okudukları okul türüne göre incelenmesi amaçlanmaktadır. Verilerin SPSS paket programına girilip daha sonra okul türlerine göre analiz edildiği bu çalışmanın önleyici rehberlik kapsamında da iyileştirici ve öğretici olması yönünden önemli bir konu olacağı düşünülmektedir. Araştırmanın örneklemi, 6 Anadolu, 2 İmam Hatip, 1 Meslek, 1 Fen, 1 Sosyal Bilimler, 1 Spor, 1 Güzel Sanatlar olmak üzere 13 okuldan ve toplam 1251 öğrenciden oluşmaktadır. Örneklem seçilirken evren temsiliyeti göz önünde bulundurulmuş, Anadolu liselerinin sayıca fazla olmasından dolayı daha fazla Anadolu lisesine uygulama yapılmıştır. Bu araştırmada veri toplama aracı olarak Arıcak, Tanrıkulu ve Kınay (2012) tarafından geliştirilmiş olan 24 madde ve tek alt boyuttan oluşan Siber Mağduriyet Ölçeği kullanılmıştır. Araştırma sonunda anadolu ve fen liseleri karşılaştırmasında anadolu liseleri lehine, anadolu ve imam hatip liseleri karşılaştırmasında imam hatip lisesi lehine bir sonuç elde edilmiştir.
Ortaöğretim Öğrencilerinin Siber Mağduriyet Durumlarının Okul Türlerine Göre İncelenmesi
Keywords: School Counseling; Okul Psikolojik Danışmanlığı